La gestion controversée du feu dans les forêts nationales de l’Idaho et de l’ouest du Montana - Nicolas Barbier (Revue de Géographie Alpine, 2015)
In Idaho and Montana just like in the rest of the U.S. Rocky Mountains, a part of the population wants to settle near forests perceived as environmental amenities. The regional net migration has been positive for about twenty-five years. Wildfires with variable intensity regularly destroy properties. Some of them kill people. Regionally, they are an important human, economic, political and environmental issue. Their significance is likely to increase due to global warming. A lot of these fires are ignited within the huge national forests of the montane zone (600 to 2,100 meters of elevation in the study area) dominated by Ponderosa pines and Douglas firs. Between the end of the conquest of the West and the 1970s, land uses have altered these forests and the fire regimes that affect them. For about four decades, managers have been involved in a partial and controversial restoration of pre-conquest fire regimes and forests they used to shape.